Clinical features affecting efficacy of immune checkpoint inhibitors in pretreated patients with advanced NSCLC: a Danish nationwide real-world study. (3rd April 2022) - Mouritzen, Mette T.; Junker, Karen F.; Carus, Andreas; Ladekarl, Morten; Meldgaard, Peter; Nielsen, Anders W. M.; Livbjerg, Anna; Larsen, Jacob W.; Skuladottir, Halla; Kristiansen, Charlotte; Wedervang, Kim; Schytte, Tine; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) are implemented as standard treatment for patients with advanced non-small cell lung cancer (NSCLC) in first-line and subsequent-line treatment. However, certain subgroups such as patients with older age, poor performance status (PS), and severe comorbidity are underrepresented in the randomized controlled trials (RCTs). This study aimed to assess overall survival (OS), treatment data, and clinical features affecting second- or subsequent-line ICI efficacy in an unselected, Danish, nationwide NSCLC population. Methods: Patients with advanced NSCLC who started nivolumab or pembrolizumab as second-line or subsequent-line treatment between 1 September 2015, and 1 October 2018, were identified from institutional records of all Danish oncology departments. Clinical and treatment data were retrospectively collected. Descriptive statistics and survival analyses were performed. Results: Data were available for 840 patients; 49% females. The median age was 68 years (19% were ≥75 years), 19% had PS ≥2, and 36% had moderate to severe comorbidity. The median OS (mOS) was 12.2 months; 15.1 months and 10.0 months in females and males, respectively. The median time-to-treatment discontinuation (mTTD) and median progression-free survival (mPFS) was 3.2 and 5.2 months, respectively. Patients with PS ≥2 had a mOS of 4.5 months, mTTD of 1.1 month, and mPFS of 2.0 months. In multivariable Cox regression analysis, male sex (HR = 1.35, 95% CI 1.11–1.62), PS >0 (PS 1, HR = 1.88, 95% CI 1.52–2.33; PS ≥2, HR = 4.15, 95% CI 3.13–5.5), liver metastases (HR = 1.72, 95% CI 1.34–2.22), and bone metastases (HR = 1.27, 95% CI 1.03–1.58) were significant poor prognostic OS factors. Conclusions: Danish real-world patients with advanced NSCLC treated with second- or subsequent-line ICI had an OS comparable to results from RCTs. Women, frail and older patients constituted a higher proportion than in previous RCTs. Clinical features associated with poor OS were male sex, PS ≥1 (in particular PS ≥2), bone-, and liver metastases.